2022
DOI: 10.1002/hrm.22101
|View full text |Cite
|
Sign up to set email alerts
|

The role of perceived workplace safety practices and mindfulness in maintaining calm in employees during times of crisis

Abstract: While prior studies in human resource management have investigated how employee outcomes have been affected in high-risk workplaces, this study stands out by examining this issue through the role played by COVID-19 as a specific stressor. We explained how employees' perceived health risks due to COVID-19 (CV19PHR) and perceived workplace safety practices (PWSPs) affected job performance via burnout and how PWSPs moderated the CV19PHR-burnout and CV19PHR-JP relationships. We also examined how mindfulness modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 90 publications
(258 reference statements)
0
25
0
Order By: Relevance
“…Further, scholars may want to examine the possibility of intercultural differences when it comes to employees from different cultural backgrounds and the way they tend to deal with environmental disruptions. For example, in this issue, Vu et al (2022) demonstrated that Vietnamese employees worry about their job security during various disasters and, therefore, work harder than in "normal" times. In contrast, employees in the United Kingdom (Barclay et al, in this issue) do not passively accept the disruptions imposed on them but, rather, proactively respond to such disruptions and resulting workplace changes by, for instance, crafting their own jobs.…”
Section: Shrm To Build Organizational Resilience Against Environmenta...mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, scholars may want to examine the possibility of intercultural differences when it comes to employees from different cultural backgrounds and the way they tend to deal with environmental disruptions. For example, in this issue, Vu et al (2022) demonstrated that Vietnamese employees worry about their job security during various disasters and, therefore, work harder than in "normal" times. In contrast, employees in the United Kingdom (Barclay et al, in this issue) do not passively accept the disruptions imposed on them but, rather, proactively respond to such disruptions and resulting workplace changes by, for instance, crafting their own jobs.…”
Section: Shrm To Build Organizational Resilience Against Environmenta...mentioning
confidence: 99%
“…We need to further extend our knowledge about HR practices and policies that will mitigate employees' stress caused by environmental disruptions. Two studies in this special issue show that an organization's tangible support for a disastrous event is essential to mitigate employees' stress (Mihalache & Mihalache, 2022; Vu et al, 2022). One promising avenue for future research is to build on HR process literature that focuses on the processes through which HR practices generate their outcomes (Sanders & Yang, 2021).…”
Section: Future Research Avenuesmentioning
confidence: 99%
“…The COVID-19 pandemic has caused several devastating consequences in many sectors around the world and in different aspects of life, such as the economy, society, and public health in particular (Nicola et al, 2020 ; Pak et al, 2020 ; Vo-Thanh et al, 2021 , 2022 ; Vu et al, 2022 ). In addition, this pandemic has destructive psychological outcomes on mental health symptoms, partially relying on individuals’ features (Reilly et al, 2021 ), including university students (Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We assessed mindfulness with five items from Brown and Ryan’s Mindful Attention and Awareness Scale, adapted by Hülsheger et al [ 32 , 68 ]. Ni et al demonstrated that this scale has excellent reliability and validity for Chinese individuals [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…In response to previous calls for longitudinal studies to further explore the relationship between parenting styles and suicidal ideation [ 13 ], this study proposes that harsh parenting, a family stressor, may lead to adolescent depressive symptoms and then trigger suicidal ideation based on COR theory. Moreover, mindfulness, a key personal resource [ 31 , 32 ], may play an important role in mitigating and preventing the loss spiral and thus moderate the effects of harsh parenting on depressive symptoms and suicidal ideation. Therefore, this study theoretically proposes an integrated model to understand the relationship between harsh parenting and suicidal ideation in Chinese adolescents (see Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%